Restoring the balance: women's experiences of retiring from elite sport - Albion, M. J. (Education, Employment, and Everything. The triple layers of a woman`s life, 2007)
Being an elite athlete requires single-minded determination, commitment, and focus on sport. These can have a detrimental effect on long-term career plans, with decisions and preparations for life after sport being put on hold for a time, or being given a lower priority. In order to assist athletes take a longer-term and more holistic view of their life goals, the Athlete Career and Education (ACE) program was developed through the Australian Institute of Sport. This paper presents a brief overview of a 5-year longitudinal study which was conducted to evaluate the effectiveness of the ACE program and looks specifically at the sport and retirement experiences of four female elite-level athletes: three netballers, and a gymnast.